Characterization of mycobacteria isolated from the Brazilian Atlantic Forest: a public health and bioprospection perspective - Emmerick, Leandro Santiago; Schwarz, Marcos Gustavo Araujo; Corrêa, Paloma Rezende; Piñero, Sindy Licette; Gomes, Leonardo Henrique Ferreira; Almeida, Ana Maria Mazotto; Valente, Richard Hemmi; Degrave, Wim Maurits Sylvain; Mendonça-Lima, Leila (Frontiers in Microbiology, 2025)
The Mycobacterium genus remains highly relevant today due to the rising incidence of tuberculosis and opportunistic infections caused by environmental mycobacteria. While much is known about M. tuberculosis, M. leprae and M. bovis, studies focusing on environmental mycobacteria remain limited. These microorganisms are globally distributed and have been identified in diverse biomes, including the Atlantic Forest. This study aims to provide a characterization of four mycobacterial strains isolated from the Atlantic Forest, assessing their metabolic capabilities and biotechnological potential. We investigated the presence of cellulases and proteases and conducted an initial profiling of secreted proteins. Furthermore, the examination of shared antigens and infection kinetics within macrophages offered insights into the ecological and pathogenic potential of these isolates. From a public health perspective, antigenic similarities between these environmental microorganisms and the BCG vaccine strain may influence the efficacy of BCG in protecting against diseases such as tuberculosis. Continued research on these and other environmental isolates, particularly within Brazil’s highly biodiverse ecosystems, holds promise for advancing scientific knowledge and contributing to human health.